The Effectiveness of Realistic Acceptance and Commitment Therapy and Positive Psychotherapy on Happiness and Resilience Among Divorced Women in Baghdad - Hassan Jassim Jassim, Heba; Mahdad, Ali; Radhawi, Saad Naeem; Golparvar, Mohsen (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the effectiveness of realistic acceptance and commitment therapy (ACT) and positive psychotherapy on happiness and resilience among divorced women in Baghdad. Methods and Materials: The research employed a quasi-experimental design with a pretest-posttest format, including two experimental groups and one control group. The statistical population consisted of all divorced women in Baghdad, from which 45 women were selected through convenience sampling based on inclusion and exclusion criteria and randomly assigned to research groups. While the control group was on a waiting list, both experimental groups received ten sessions of realistic ACT training (Afshari et al., 2022) and positive psychotherapy (Elmimanesh & Zhaleh, 2018). All participants were assessed using the Happiness Questionnaire (Hills & Argyle, 2002) and the Resilience Scale (Connor & Davidson, 2003) before, immediately after, and 45 days following the interventions. The collected data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures ANOVA). Findings: The results indicated that both approaches significantly increased happiness and resilience. Conclusion: Based on the findings, it can be concluded that these methods are effective in improving happiness and resilience among divorced women in Baghdad. It is recommended that policymakers and health sector officials prioritize implementing these intervention packages through trained psychologists for divorced women.